2013
DOI: 10.1111/ajt.12351
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin Augments Human DC IL-12p70 and IL-27 Secretion to Promote Allogeneic Type1 Polarization Modulated by NK Cells

Abstract: Mammalian target of rapamycin kinase inhibitor (mTORi) rapamycin (RAPA) use in transplantation can lead to inflammatory complications in some patients. Our goal was to better understand how mTORi-exposed human monocyte-derived dendritic cells (DC) stimulated with pro-inflammatory cytokines shape T cell allo-immunity. RAPA-conditioned-DC (RAPA-DC) displayed a more immature phenotype than untreated, control (CTRL)-DC. However, subsequent exposure of RAPA-DC to an inflammatory cytokine cocktail (ICC) plus IFN-γ i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
35
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 52 publications
3
35
0
Order By: Relevance
“…In a recent study, Macedo et al (72) found that while RAPAtreated cDC generated from healthy volunteers displayed an ''immature'' phenotype, subsequent exposure to an inflammatory cytokine cocktail plus IFN-g induced a mature, type-1-promoting, immunostimulatory phenotype. This was characterized by elevated cell surface HLA-DR and co-stimulatory molecules, augmented IL12p70 and IL-27 production and decreased IL-10 secretion.…”
Section: Nk Cellsmentioning
confidence: 99%
“…In a recent study, Macedo et al (72) found that while RAPAtreated cDC generated from healthy volunteers displayed an ''immature'' phenotype, subsequent exposure to an inflammatory cytokine cocktail plus IFN-g induced a mature, type-1-promoting, immunostimulatory phenotype. This was characterized by elevated cell surface HLA-DR and co-stimulatory molecules, augmented IL12p70 and IL-27 production and decreased IL-10 secretion.…”
Section: Nk Cellsmentioning
confidence: 99%
“…22 It has been reported that in response to increased levels of IL-12p70, natural killer cells release large amounts of IFN-g and nitric oxide. 22,23 This undesirable induction has been shown with the use of rapamycin as an immunosuppressant, but was not seen with reparixin in this study. 23 Since reparixin is involved in the activation of CXCR1/2 and neutrophil recruitment, one additional cytokine that may be important to measure is the neutrophil activating factor IL-8, a mediator of both cytokine cascades and neutrophil responses.…”
Section: Discussionmentioning
confidence: 50%
“…22,23 This undesirable induction has been shown with the use of rapamycin as an immunosuppressant, but was not seen with reparixin in this study. 23 Since reparixin is involved in the activation of CXCR1/2 and neutrophil recruitment, one additional cytokine that may be important to measure is the neutrophil activating factor IL-8, a mediator of both cytokine cascades and neutrophil responses. 21 The KC receptor and the IL-8 type B receptor are homologous and mouse KC also known as CXCL1, neutrophil-activating protein 3 (NAP-3) is involved in chemotaxis and cell activation of neutrophils.…”
Section: Discussionmentioning
confidence: 50%
“…In addition, absence of MyD88 signaling resulted in reduced mRNA expression of IL-1 family cytokines [14]. IL-1 was not required for the growth of established human Th1 or Th2 clones, but it played a critical role in the development of Th2 cells, whereas Th1 development was unaffected [23]. Decrease of IL-1 family cytokines will also affect Th17 development.…”
Section: Discussionmentioning
confidence: 99%
“…Release of IL-12 by DCs promotes Th1 cells, which produce high levels of IFN-g and IL-2. Th2 cells are stimulated through OX40 ligation by DCs, and produce IL-4, IL-5 and IL-13 [23,24]. Tumor-growth factor-b (TGF-b), IL-1 and IL-6 induce the production of Th17, which is characterized by the production of IL-17A, IL-17F, IL-8, IL-21 and IL-22.…”
Section: Discussionmentioning
confidence: 99%